The 10th GCC Closed Forum: rejected data, GCP in bioanalysis, extract stability, BAV, processed batch acceptance, matrix stability, critical reagents, ELN and data integrity and counteracting fraud. (April 2017) - Cape, Stephanie; Islam, Rafiq; Nehls, Corey; Allinson, John; Safavi, Afshin; Bennett, Patrick; Hulse, James; Beaver, Chris; Khan, Masood; Karnik, Shane; Caturla, Maria Cruz; Lowes, Steve; et al.
The 10th Global CRO Council (GCC) Closed Forum was held in Orlando, FL, USA on 18 April 2016. In attendance were decision makers from international CRO member companies offering bioanalytical services. The objective of this meeting was for GCC members to meet and discuss scientific and regulatory issues specific to bioanalysis. The issues discussed at this closed forum included reporting data from failed method validation runs, GCP for clinical sample bioanalysis, extracted sample stability, biomarker assay validation, processed batch acceptance criteria, electronic laboratory notebooks and data integrity, Health Canada's Notice regarding replicates in matrix stability evaluations, critical reagents and regulatory approaches to counteract fraud. In order to obtain the pharma perspectives on some of these topics, the first joint CRO–Pharma Scientific Interchange Meeting was held on 12 November 2016, in Denver, Colorado, USA. The five topics discussed at this Interchange meeting were reporting data from failed method validation runs, GCP for clinical sample bioanalysis, extracted sample stability, processed batch acceptance criteria and electronic laboratory notebooks and data integrity. The conclusions from the discussions of these topics at both meetings are included in this report.